2022
DOI: 10.2106/jbjs.oa.21.00113
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Educational Resources for the Aspiring Orthopaedic Surgeon

Abstract: Musculoskeletal (MSK) education is underemphasized in medical school curricula, which can lead to decreased confidence in treating MSK conditions and suboptimal performance on orthopaedic surgery elective rotations or subinternships. Given the low amount of formalized education in MSK medicine, students aiming to learn about orthopaedic surgery must gain much of their foundational knowledge from other resources. However, there are currently no centralized introductory educational resources to fill this need. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This view was supported by a study by Wadhwa et al . [ 10 ] on the musculoskeletal educational resources for future aspiring orthopaedic surgeons. However, from our study, about 29 respondents said they had a club journal in their school, out of which only 17.65% are members.…”
Section: Discussionmentioning
confidence: 99%
“…This view was supported by a study by Wadhwa et al . [ 10 ] on the musculoskeletal educational resources for future aspiring orthopaedic surgeons. However, from our study, about 29 respondents said they had a club journal in their school, out of which only 17.65% are members.…”
Section: Discussionmentioning
confidence: 99%
“…A survey revealed that only 54% of medical students felt their MSK education was adequate ​[ 7 ]. Furthermore, only 83% of medical schools require pre-clinical MSK education, and a mere 15% mandate an MSK clerkship ​[ 8 ]. This variability in UME MSK curricula underscores the challenge of defining essential foundational MSK education.…”
Section: Introductionmentioning
confidence: 99%